Employee retention strategies in IT sector – a perceptual survey - V.J., DR. MAHESH; K.R., NARMADHA (The journal of contemporary issues in business and government, 2020)
This study has been conducted to examine Employee Retention Strategy used in the IT sector to retain their employees. Employee Retention refers to the different practices which let the employees retain in an organisation for a longer period of time. Each organisation invests time and cash to prepare a new employee, make him a corporate prepared material and carry him at standard with the current employees. The organisation is totally at loss when the employees give up positions once they are completely prepared. Employee retention considers the different estimates taken with the goal that an individual stays in an organisation for the greatest timeframe. Retention strategies are policies and plans that organisations follow to decrease worker turnover and attrition and guarantee employees are locked in and gainful long haul. The critical test for organizations is guaranteeing a retention methodology lines up with business objectives to guarantee the most extreme degree of profitability. The questionnaire was conducted to gather primary data, and it is directly led from the employees to recognize the elements that make them resolved to serve their current organisation. The findings of the study reveals that the increase in rewards and recognition, good working environment, supervisor support and contribution of increased supervisor support career opportunity has a positive significant impact on Employee Retention in the IT sector.